Heat Mode Electronic Devices at Elevated External Temperatures; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Kravchenko E. V. Evgeny Vladimirovich (2016, 2016)
Title screen